Sustainable Maritime Education and Workforce Development: Curriculum Design, Competency Enhancement, and Skills Training for Green Shipping Professionals - Rosna Yuherlina Siahaan; Derma Watty Sihombing; Tri Kismantoro (Global Research Collaboration, 2026)
The maritime industry's accelerating transition toward decarbonization and sustainable operations has exposed a critical misalignment between existing maritime education systems and the competency demands of green shipping. This study examines the design, implementation, and effectiveness of sustainable maritime education and workforce development programs, focusing on curriculum innovation, competency enhancement strategies, and skills training models for green shipping professionals. Employing a qualitative research design that integrates thematic analysis, cross-group comparison, and narrative synthesis, the study draws upon expert consultations and document analysis involving maritime educators, industry professionals, and recent graduates from maritime training institutions. The findings reveal four principal themes: the reconceptualization of maritime competency frameworks to incorporate sustainability literacy, the pedagogical transformation required for experiential and interdisciplinary curriculum delivery, the critical role of organizational culture and institutional readiness in enabling educational reform, and the necessity of multi-stakeholder collaboration in aligning education with industry demands. The study contributes a competency-curriculum alignment model that bridges the gap between green shipping workforce requirements and maritime education provision, offering actionable guidance for maritime training institutions, regulatory bodies, and industry stakeholders committed to building a sustainability-competent maritime workforce.